Recommendations for Intra-abdominal Infections Consensus Report - Oguz, Vildan Avkan; Baykam, Nurcan; Sokmen, Selman; Guner, Rahmet; Agalar, Fatih; Mese, Emine Alp; Koksal, Iftihar (Galenos Yayincilik, 2016)
Guidelines include recommendations of experts from various specialties within a topic in consideration of data specific to each country. However, to date there has not been a guideline standardizing the nomenclature and offering recommendations for intra-abdominal infections (IAIs) in Turkey. This is mainly due to the paucity of laboratory studies regarding the clinical diagnosis and treatment of IAIs or the sensitivity of microorganisms isolated from patients with IAIs. However, due to the diversification of host characteristics and advancements in technological treatment methods, it has become imperative to speak a common language. For this purpose, meetings were formed under the leadership of the Infectious Diseases and Clinical Microbiology Specialty Society of Turkey (EKMUD) consisting of 15 experts in IAIs from the Turkish Surgical Association, Turkish Society of Colon, Turkish Hernia Society, Turkish Society of Hepato-Pancreato-Biliary Surgery, and the Turkish Society of Hospital Infections and Control; and relevant studies were analyzed.. Ultimately, the suggestions for adults found in this consensus report were prepared using available data from Turkey, and referring predominantly to the 2010 guidelines for diagnosing and managing complicated IAIs in adults and children by the Infectious Diseases Society of America and the Surgical Infection Society. Recommendations are conducted in two sections from the initial evaluation of patients for diagnosis to treatment approach for IAI. This Consensus Report was presented in Turkey EKMUD 2016 Congress/Antalya and subsequently opened for any suggestions in Turkey EKMUD and Turkish Surgical Association official web sites for a month. The manuscript was updated according to the suggestions.
Keywords: Intra-abdominal infection; intraabdominal; management; recommendations; guideline